2019
DOI: 10.1111/jch.13658
|View full text |Cite
|
Sign up to set email alerts
|

Impaired orthostatic blood pressure stabilization and reduced hemoglobin in chronic kidney disease

Abstract: Impaired orthostatic blood pressure (BP) stabilization is prevalent in patients with chronic kidney disease (CKD) and is associated with adverse outcomes. We aimed to test the hypothesis that reduced hemoglobin is an important contributor to orthostatic intolerance in CKD in the present study. This study included 262 patients with non-dialysis-dependent CKD. Seated and standing BP was measured, and orthostatic BP reduction was calculated for both systolic BP (∆ SBP) and diastolic BP (∆ DBP).The association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Several factors that may contribute to alterations in blood pressure compensation with standing are J o u r n a l P r e -p r o o f present in patients with CKD; these include arterial stiffness, anemia, and impaired autonomic function, among other determinants. [26][27][28] Whether these factors mediate the relationship between orthostatic hypotension and cardiovascular outcomes needs to be evaluated in future studies. As expected, individuals with diabetes have a high prevalence of orthostatic hypotension likely secondary to autonomic neuropathy, and impaired baroreceptor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that may contribute to alterations in blood pressure compensation with standing are J o u r n a l P r e -p r o o f present in patients with CKD; these include arterial stiffness, anemia, and impaired autonomic function, among other determinants. [26][27][28] Whether these factors mediate the relationship between orthostatic hypotension and cardiovascular outcomes needs to be evaluated in future studies. As expected, individuals with diabetes have a high prevalence of orthostatic hypotension likely secondary to autonomic neuropathy, and impaired baroreceptor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification is also another common complication of CKD [ 33 ]. Liu et al also found that orthostatic hypotension in CKD is closely related to haemoglobin reduction [ 34 ]. Lower ALB, serum CHOL, and TGs are key factors in anaemia and may represent a state of malnutrition in the body, which is also closely related to anaemia because of chronic inflammation in CKD [ 7 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is a natural antioxidant compound with beneficial characteristics, but preclinical studies have demonstrated that it is also a proinflammatory compound, and an elevated uric acid level has been found to be associated with the risk of myocardial infarction, stroke, and cardiovascular mortality [18]. On the other hand, OH is already seen at a high rate in CKD patients, and many risk factors in CKD patients, just like DM, can cause arterial stiffness, anemia, impairment of sympathetic nervous system function, and autonomic dysfunction [19,20]. In this study, it was shown for the first time that whether the etiology of CKD is DNP or not does not influence the OH prevalence in these patients.…”
Section: Discussionmentioning
confidence: 99%